Signal transduction by the 5-HT2A receptor and its H452Y polymorphic variant - Barclay, Zoë Jade (The University of Edinburgh, 2010)
The 5-HT2A receptor (5-HT2AR) is implicated in neuropsychiatric disorders such as schizophrenia and is thought to mediate the actions of a number of hallucinogenic and antipsychotic drugs. Additionally, certain polymorphic variants of the receptor, such as an allele resulting in substitution of amino acid 452 histidine (H) with tyrosine (Y), have been linked to schizophrenia or altered therapeutic response to antipsychotics. The 5-HT2AR utilises various intracellular signalling pathways, including the activation of phospholipase C (PLC) and phospholipase D (PLD) via recruitment of the small G-protein ADP-Ribosylation Factor (ARF). This thesis focusses on protein:protein interactions and signalling mechanisms of the 5-HT2AR and H452Y-5-HT2AR receptor variant. Both ARF1 and PLD1 have previously been shown to bind to the carboxy-terminal tail (ct) of the 5-HT2AR. In chapter three it is demonstrated that the 5-HT2AR can activate PLD in an ARF-dependent manner, primarily through the PLD1 isoform. GST-fusion proteins of truncated and mutated variants of the receptor ct are used to show that ARF1 and PLD1 independently bind to distinct sites. Coimmunoprecipitation, GST-fusion protein studies and PLD activity assays demonstrate that the introduction of the H452Y mutation decreases the physical interactions between the receptor and PLD1, as well as decreasing 5-HT2ARmediated PLD activation. In chapter four, potential mechanisms of wild-type and H452Y-5-HT2AR desensitisation are explored. It is shown that β-arrestin 2 (β-arr 2) confers a decrease in H452Y-5-HT2AR-mediated PLC activity, despite having no significant effect upon wild-type 5-HT2AR responses. The H452Y-5-HT2AR variant is also shown, by GST-fusion protein studies, to bind β-arr 2 more strongly. The H452Y-5-HT2AR additionally mediates increased levels of 5-HT-induced ERK phosphorylation compared to the wild type 5-HT2AR, potentially through increased scaffolding of ERK activation complexes by receptor-bound β-arr 2. Chapter five focusses on possible interactions of the 5-HT2AR with the Ca2+-binding proteins annexin A2, S100B and the annexin A2 partner p11, together with the functional consequences of these interactions. Co-immunoprecipiation and GST-fusion protein studies show that annexin A2 binds specifically to the 5-HT2AR ct. Furthermore, annexin A2 (but not S100B or p11) is shown to result in an amplification of 5-HT2AR-mediated PLC responses. These findings provide a greater insight into some of the signal transduction mechanisms of the 5-HT2AR and their perturbation in the H452Y polymorphic form of the receptor, and understanding of the molecular mechanisms underlying neuropsychiatric diseases in patient subgroups, potentially leading to improved therapeutic treatments.
Keywords: 5-HT2AR receptor; PLD; phospholipase D; H452Y